Webometric as diagnostic tools of digital sociology: contents, purpose, usage experience - M. V. Kibakin (Цифровая социология, 2020)
The essence of Webometrics as a sociological method of collecting primary material by studying the content of content, services and the convenience of technological solutions for accessing it by users has been revealed in the article. A justification for the need to develop digital technologies for social diagnostics using webometric indicators has been provided. Based on the analysis of scientific sources on the problem, the significant potential of Webometrics in the study of various aspects of scientific, educational, and political activities, as well as its universal character as a methodological tool have been shown.A refined concept of Webometrics as a method of collecting primary sociological data has been given, the possibility of using it to study Internet content has been described. The rules and conditions for effective use of Webometrics have been substantiated, based on the usage of content analysis methods and procedures for the development of its forms; to include usability and visibility in the analysis of technological characteristics of Internet portals; to make the research parameters used reliable by separating them from official documents of state policy and corporate strategies; to combine traditional methods of fixing primary data and computer algorithms. A specific webometric technique has been revealed in detail, which implies fixing the formal status of the Internet source under study, the content parameters of information representation of information about the implementation of state policy on the example of working with young people, the availability of services, as well as indicators of the site’s technology and ease of access to it by the population. An example of obtaining data on the basis of Webometrics, as well as its interpretation has been given.Based on the data obtained, an analysis of the combination of traditional and modern interactive services, which are currently presented on official websites, has been made, the shortcomings of the existing situation for effective information policy in the field of work with young people have been shown. It has been concluded about the relevance of webometric methods and the great potential for their development within the framework of digital sociology.